Colonization and urbanization of the West Region of Paraná State (1940-2000) - Reolon, Cleverson Alexsander (2007)
This paper aims at analysing the demographic dynamics ofthe West Region of Paraná State starting from the last phaseof its occupation until the end of the century, in other words,since 1940 until 2000. The demographic indicators denote afast occupation process of the region, suggesting a growingtendency of its urbanization, that already reached high value,superior of the Paraná State. It was concluded that it’s betterto be attempt for the quality of this process, especially for themunicipalities that are considered areas with concentrationof population.